Medieval Greek commentaries on the Nicomachean ethics - Barber, Charles; Jenkins, David (Studien und Texte zur Geistesgeschichte des Mittelalters, 2009)
Classical scholarship in twelfth-century Byzantium / Anthony Kaldellis -- The literary, cultural and political context for the twelfth-century commentary on the Nicomachean ethics / Peter Frankopan -- The Aristotelian ethics in Byzantium / Linos G. Benakis -- Neoplatonic source-material in Eustratios of Nicaea's commentary on Book VI of the Nicomachean ethics / Michele Trizio -- Eustratios of Nicaea's 'Definition of being' revisited / David Jenkins -- Eustratios of Nicaea on the separation of art and theology / Charles Barber -- The anonymous commentary on Nicomachean ethics VII : language, style, and implications / Elizabeth A. Fisher -- Michael of Ephesus on the empirical man, the scientist and the educated man (in Ethica Nicomachea X and in De partibus animalium I) / George Arabatzis -- Some observations on Michael of Ephesus' comments on Nicomachean ethics / Katerina Ierodiakonou